IMPROVING NATURAL SCIENCE LEARNING ACTIVITIES AND OUTCOMES THROUGH AN "INTERNAL" LEARNING MODEL - Jannah, Fathul; Sari, Raihanah; Prihandoko, Yogi; Dwi Prasetyo, Yogo; Indriati, Sonia (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
Students’ low learning activity and outcomes in natural sciences learning are the problem discussed in this paper. The INTERNAL model integrates Inquiry, Number Head Together, and snowball throwing. This paper uses a qualitative approach and classroom action research (CAR), which was held for four meetings. Data analysis were teacher activity sheets, students’ learning activity sheets, and students’ learning outcomes sheets. Data collection techniques were observation and writing tests. The research subjects were 32 fifth-grade students of SDN Swato 2 Tapin for the academic year 2021/2022. The indicator of the success of students’ learning activity score was 58-72, and students’ learning outcomes, which has minimum standards under 70 with a classical percentage above 80%. The research results indicate that the teacher's teaching activity at the first meeting, which achieved 54 in the good category, increased to 74 in the very good category at the fourth meeting. Students’ learning activity classically at the first meeting that achieved 25% in a highly active category increased to 83,3% with a highly active category at the fourth meeting. Students’ learning outcomes at the first meeting with 50% classical completeness increased to 100% classical completeness at the fourth meeting. It can be concluded that applying the internal learning model can improve students’ learning activities and outcomes.